Buya Ahmad Syafii Maarif’s Islamic Thought: Morality, Nationalism, and Humanity - Gusnanda Eljambaki (Universitas Islam Negeri Imam Bonjol Padang, 2025)
This article examines the distinctive Islamic thought of Buya Ahmad Syafii Maarif, a prominent Indonesian Muslim intellectual whose ideas integrate morality, nationalism, and humanity. Unlike political interpretations of Islamism, Buya Syafii emphasized a moral-ethical framework of Islam as the foundation for responding to radicalism, identity politics, and moral decline. Using a qualitative library research method, this study analyzes his major works, writings of his disciples, and relevant literature. The findings show that Buya Syafii consistently placed morality at the core of Islamic interpretation, rejecting religious symbolism devoid of substance, and strongly criticizing transnational radicalism that threatens Indonesian unity. His intellectual contribution lies in positioning Islam not only as a personal faith but also as a moral force that upholds justice, inclusivity, and solidarity. Concretely, he integrated Qur’anic ethics with the spirit of Indonesian nationalism and universal human values, offering a model of “moral Islam” that resists exclusivism and violence. Theoretically, this study contributes by mapping Buya Syafii’s thought as a framework of moral Islam in contemporary Indonesian discourse. Practically, it proposes the internalization of these values in education, public debate, and religious movements to strengthen an inclusive and humane Indonesian Islam.